2012
DOI: 10.1590/s1678-77572012000600010
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength between acrylic resin and maxillofacial silicone

Abstract: The development of implant dentistry improved the possibilities of rehabilitation with maxillofacial prosthesis. However, clinically it is difficult to bond the silicone to the attachment system.ObjectivesThis study aimed to evaluate the effect of an adhesive system on the bond strength between acrylic resin and facial silicone. Material and MethodsA total of 120 samples were fabricated with auto-polymerized acrylic resin and MDX 4-4210 facial silicone. Both materials were bonded through mechanical retentions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 23 publications
0
39
0
1
Order By: Relevance
“…Shetty 8) studied the effect of primers on maxillofacial silicon and three types of surface-characterized acrylic resin, concluding that primers were more compatible with silicone elastomer and also that the presence of retentive holes increased bond strength. Haddad 14) et al also reported that primer use increased bond strength between autopolymerized acrylic resin and facial silicone elastomer. Therefore, primer use on an acrylic plate is generally considered to be conducive to silicone elastomer bonding.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Shetty 8) studied the effect of primers on maxillofacial silicon and three types of surface-characterized acrylic resin, concluding that primers were more compatible with silicone elastomer and also that the presence of retentive holes increased bond strength. Haddad 14) et al also reported that primer use increased bond strength between autopolymerized acrylic resin and facial silicone elastomer. Therefore, primer use on an acrylic plate is generally considered to be conducive to silicone elastomer bonding.…”
Section: Discussionmentioning
confidence: 97%
“…Unifast is used for temporary prostheses, denture repair 23) , and attaching housing to the facial prostheses 9) . The bonding of silicone on an acrylic plate was reported very poor when bonded without a primer 8,14,24) . Therefore, the bond strength between silicone and acrylic without a primer was not examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They used different primers and surface modification (scratch) to check the effect of bond strength and concluded that use of primer increased the bond strength but use of primer along with the surface modification (scratch) has weakened the bond strength between silicone elastomer and acrylic [14].…”
Section: Discussionmentioning
confidence: 99%